Integration of Information and Communication Technology in Pedagogy: A Systematic Review of Literature - Joshi, Bishnu Maya (Mangal Research Journal, 2022)
This paper examines an effective integration of information and communication technology (ICT) in pedagogy in an educational setting. Presently, teaching-learning activities in higher education are becoming more complex and challenging. Therefore, knowledge of the content alone is insufficient to teach social sciences in higher education specified by the curriculum. The knowledge and skills of modern information and communication technology have become equally essential for a skilled teacher to have effective teaching and learning. This study aims to analyze teachers' perceptions of the importance of ICT integration in pedagogy at higher levels of education. Thus, this paper focuses on integrating information and communication technology in pedagogy. It is integral to education in many developing countries, including Nepal. The connotations of information and communication technology have been used variously in teaching. All the electronic materials including computer technology used in teaching-learning activities are considered information and communication technology (ICT). A systematic review of literature on 'Importance of ICT in education and 'Teacher's perception on the integration of ICT in pedagogy' with the theoretical base of content knowledge (CK), pedagogical knowledge (PK), and pedagogical and content knowledge (PCK) with ICT are the main bases of this study. Information was collected from the review of 14 articles published from 2013-2020 in English, which covers teachers' views and perceptions on integrating ICT in pedagogy. The findings indicate that teachers can inevitably use ICT to deliver content effectively and fulfil students' 21st-century ICT needs by integrating pedagogical content knowledge with ICT.